Lotus spp: Biotechnological strategies to improve the bioeconomy of lowlands in te Salado River Basin (Argentina) - Antonelli, Cristian Javier (2016)
The Salado River Basin region is the most important livestock breeding area in Argentina, wherethe Lotus species has been traditionally cultivated as forages. Nearly 60% of their land surface is dominated by salt-affected soils with severe constraints for crop cultivation. In order to cope with that limitation, farmers have utilized species such as non-native L. tenuis (ex- Lotus glaber), which shows a very good adaptation. As a result, inter-seeding of L. tenuis has been proposed as a strategy of choice for improving forage production in marginal areas. The increase in soil quality by these means is achieved by an increment of the organic matter content, improvement of soil fertility as well as microbial biodiversity. Thus, the introduction of L. tenuis and/or other Lotus genotypes could have enormous benefits for similar constrained lands around the world. We are developing an integrated analysis of the changes that occur in soils under legume production. We will not only analyze the microbial diversity associated, but also soil physical and chemical characteristics and the impact of different legume-microbes association on mitigation of GHG emissions. In addition, we are identifying the main genetic determinants associated with interesting agronomic traits such as plant tolerance against biotic and abiotic stresses and the content of condensed tannins. Our future and present research will build a solid base for the improvement of agronomicallyimportant species and the development of better strategies for the management of constrained lands such as the lowlands in the Argentinean Pampas.